Consumer purchase intentions for green products: Mediating role of WTP and moderating effects of framing. Issue 4 (3rd July 2016) - Ayadi, Nawel; Lapeyre, Alexandre
Abstract : This research examines the role of consumers' willingness to pay (WTP) in the purchase decision process for a green product and investigates the moderating effects of two types of framing: price and ecological message claim. Using an experimental design, 262 participants were assigned randomly to one of nine conditions (3 price × 3 ecological message frames). The results reveal a mediating effect of WTP on the relationship between consumers' perceptions and purchase intentions. Furthermore, a price framed in aggregate terms reinforces the positive effect of WTP on purchase intention. The mere presence of an ecological message claim also enhances the relation between WTP and purchase intentions. This research proposes ways marketers can promote their green products. The results encourage the use of ecological messages and frames of prices in an aggregate form to enhance consumers' purchase intentions through WTP.